Dating Amber [videorecording (DVD)] - Freyne, David; Petticrew, Lola; Horgan, Sharon, 1970-; O'Shea, Fionn; Ward, Barry, 1971- (Samuel Goldwyn Films, 2020)
In Ireland during the mid-90s, two teens still figuring out their sexuality decide to pretend to date in order to keep other people out of it. When their "ideal" arrangement begins to fall apart, Eddie spirals and Amber realizes just how much danger he could be in